2020
DOI: 10.1186/s12887-020-02172-z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of gamma-glutamyl transferase and liver stiffness measurement for biliary atresia screening at different ages: a retrospective analysis of 282 infants

Abstract: Background This study aims to explore the diagnostic accuracy of the combination of gamma-glutamyl transferase (GGT) and liver stiffness measurement (LSM) for biliary atresia (BA) screening at different ages. Methods Our retrospective study involved 282 infants under the age of 120 days with jaundice who were admitted into Beijing Children’s Hospital between January 2016 to December 2018. The GGT and LSM levels of infants were obtained. A parallel test was used, and ROC curve was created to obtain cutoff valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Additionally, the LSM value mainly reflects the degree of liver fibrosis, which is one of the main pathological features of BA (28). Previous studies have applied the LSM assessment for the diagnostic and prognostic prediction of BA (29)(30)(31). Wu et al found that an LSM value > 7.7 kPa was a predictive factor for discriminating BA patients from other cholestatic patients, and patients with an LSM value > 16 kPa often require early liver transplantation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the LSM value mainly reflects the degree of liver fibrosis, which is one of the main pathological features of BA (28). Previous studies have applied the LSM assessment for the diagnostic and prognostic prediction of BA (29)(30)(31). Wu et al found that an LSM value > 7.7 kPa was a predictive factor for discriminating BA patients from other cholestatic patients, and patients with an LSM value > 16 kPa often require early liver transplantation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al explored the diagnostic accuracy for BA of parallel testing of GGT and LSM by the SuperSonic system among patients with cholestasis separated into three age groups (≤60 days, n = 124; 61-90 days, n = 124; and 91-120 days, n = 34) in a retrospective study. (27) Infants younger than 30 days of age (9 patients) were not grouped separately because of the small number. The optimal cutoff LSM value in the group aged 60 days or younger was 7.5 kPa (AUC of 0.761, sensitivity of 87.8%, specificity of 58.0%).…”
Section: Discussionmentioning
confidence: 99%
“…This study was approved by the Ethics Committee of the Children's Hospital of Fudan University. We reviewed several studies on the diagnostic efficacy of GGT in differentiating BA from other cholestatic diseases and found that the threshold values in most studies were between 250 and 300 IU/L (1,4,6,(13)(14)(15). Therefore, 300 IU/L was used as the critical cut-off value differentiating the low-GGT group (≤300 IU/L) from the high-GGT group (>300 IU/L) based on the preoperative GGT level.…”
Section: Methodsmentioning
confidence: 99%
“…The serum level of gamma-glutamyl transpeptidase (GGT) in most patients with biliary atresia (BA) is significantly increased, which plays an important role in the differential diagnosis of neonatal cholestatic disorders (1)(2)(3)(4)(5)(6)(7). However, some neonates initially presenting with normal or minimally elevated GGT levels are eventually, and sometimes unexpectedly, confirmed to have BA (8,9).…”
Section: Introductionmentioning
confidence: 99%